Large B-cell non-Hodgkin lymphoma of the oral cavity: a case report and review of literature - Vinitzky Brener, Ilan (2020)
Non-Hodgkin lymphomas make up a group of malignant neoplasms of lymphoid origin, according to their corresponding cell line, as B or T cell lymphomas classified. Mostly, these entities come from B lymphocytes, being the most frequent diffuse large B-cell lymphoma (DLBCL). In the oral cavity, non-Hodgkin lymphomas have low incidence and their prognosis, clinical evolution and response to treatments, depend on the subtype presented. These malignancies can develop in soft tissues of the oral cavity or centrally in the jaws. We report an 80-year-old patient with an injury corresponding to large B-cell non-Hodgkin lymphoma in the oral cavity, who has been treated with chemotherapy and radiotherapy, responding favorably to treatment. Likewise, in order to describe this infrequent type of lesions of the oral cavity and to assess the prognosis they have, a literature review was performed. It is concluded that because of the prognosis of this type of lesions depends on the subtype of non-Hodgkin lymphoma in question and its anatomical location, it is very important to make a correct diagnosis, in order to perform the adequate treatment for each case.